2018
DOI: 10.3390/pathogens7010023
|View full text |Cite
|
Sign up to set email alerts
|

Species C Rotaviruses in Children with Diarrhea in India, 2010–2013: A Potentially Neglected Cause of Acute Gastroenteritis

Abstract: All over the world, children and adults are severely affected by acute gastroenteritis, caused by one of the emerging enteric pathogens, rotavirus C (RVC). At present, no extensive surveillance program is running for RVC in India, and its prevalence is largely unknown except cases of local outbreaks. Here, we intended to detect the presence of RVC in diarrheic children visiting or admitted to hospitals in Haldwani (state of Uttarakhand, India), a city located in the foothills of the Himalayas. During 2010–2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The extent of RVC diversity identified in US swine has important implications for pathogen control, including the development of porcine RVC vaccines. Although RVC is not considered a clinically important pathogen for human infant mortality due to its milder sporadic and outbreak cases (Bhat et al, ; Meleg et al, ; Moon et al, ), our analysis revealed that the pathogen has been established as an independent lineage in humans for decades, at least, and remains undersampled, as exposed by extremely long branch lengths in the trees. At this time, it is not possible to determine whether the multitude of independently evolving swine lineages arose from viral diversification within pigs, accruing diversity gradually over centuries, or via multiple independent viral introductions into pigs from other RVC hosts that have not been sampled.…”
Section: Discussionmentioning
confidence: 71%
“…The extent of RVC diversity identified in US swine has important implications for pathogen control, including the development of porcine RVC vaccines. Although RVC is not considered a clinically important pathogen for human infant mortality due to its milder sporadic and outbreak cases (Bhat et al, ; Meleg et al, ; Moon et al, ), our analysis revealed that the pathogen has been established as an independent lineage in humans for decades, at least, and remains undersampled, as exposed by extremely long branch lengths in the trees. At this time, it is not possible to determine whether the multitude of independently evolving swine lineages arose from viral diversification within pigs, accruing diversity gradually over centuries, or via multiple independent viral introductions into pigs from other RVC hosts that have not been sampled.…”
Section: Discussionmentioning
confidence: 71%
“…Unlikely RVA, the number of whole RVC genome data is limited. However, over the past few years, there has been an increased interest in human and porcine RVCs, and additional whole genome sequences have been published, which help elucidate their zoonotic relationship [17,33,35,37,[61][62][63][64][65][66][67]. While a clade of VP3 segments of RVC strains from humans shared a common ancestor with porcine strains, Bayesian analysis illustrated these human and porcine strains diverged over a hundred years ago [36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incidence of RVC infections among humans has increased significantly (Araújo, Heinemann, Fialho, & Leite, 2011; Bhat et al., 2018; Esona, Humphrey, Dennehy, & Jiang, 2008; Joshi, Jare, & Gopalkrishna, 2017). Consequently, it is important to monitor the occurrence of interspecies transmission, particularly that between pigs and humans.…”
Section: Discussionmentioning
confidence: 99%